Тепловой поток, термическая история материнской нижнеюрской тогурской свиты и нефтегазоносностъ палеозоя Колтогорского мезопрогиба (южный сегмент Колтогорско-Уренгойского палеорифта) - Лобова, Г.А.; Лунева, Т.Е.; Исаев, В.И.; Фомин, А.Н.; Коржов, Ю.В.; Галиева, М.Ф.; Крутенко, Д.С. (Геофизический журнал, 2019)
В воспроизведении сырьевой базы Западно центра нефтегазодобычи важным является вклад доюрской ( "палеозойской") нефти. Представляют интерес прогнозно-поисковые исследования доюрських резервуаров на территории Колтогорського мезопро-погибаю и структур его обрамления - на северо-западе Томской области, в зоне южного сегмента Колтогорсько-Уренгойского пермо-триасового палеорифту. На территории исследований наряду с меловым (неокомских), верхнеюрского, средньоюрським, нижньоюрським нефтегазоносными комплексами выделено и доюрского (горизонт зоны контакта - НГГЗК и собственно внутренний палеозой). Принято, что для се-редньоюрського, верхнеюрского и мелового нефтегазоносных комплексов материнской есть верхнеюрского баженовська света, для залежей нижньоюрського и доюрського комплексов - тогурска света. Исследование выполнено в контексте методологии осадочно-миграционной теории нафтидогенезу. Пространственно-временную локализацию очагов генерации тогурськои нефти осуществлено оригинальным методом палеотемпературного моделирования. У відтворенні сировинної бази Західносибірського центру нафтогазовидобутку важливим є внесок доюрської ("палеозойської") нафти. Становлять інтерес прогнозно-пошукові дослідження доюрських резервуарів на території Колтогорського мезопро-гину і структур його обрамлення — на північному заході Томської області, в зоні південного сегмента Колтогорсько-Уренгойського пермо-тріасового палеорифту. На території досліджень поряд з крейдяним (неокомським), верхньоюрським, средньоюрським, нижньоюрським нафтогазоносними комплексами виділено і доюрский (горизонт зони контакту — НГГЗК і власне внутрішній палеозой). Прийнято, що для се-редньоюрського, верхньоюрського і крейдяного нафтогазоносних комплексів материнською є верхньоюрська баженовська світа, для покладів нижньоюрського і доюрського комплексів — тогурска світа. Дослідження виконано у контексті методології осадово-міграційної теорії нафтидогенезу. Просторово-часову локалізацію осередків генерації тогурської нафти здійснено оригінальним методом палеотемпературного моделювання. Input of the pre-Jurassic («Paleozoic») oil is important to the reproduction of the in-situ resources base of Western Siberian oil and gas extraction. Prospecting and forecasting studies of the pre-Jurassic reservoirs in the territory of the Koltogor mezodepression and structures of its surrounding — in the north-western part of Tomsk Region, in the zone of the southern segment of the Koltogor-Urengoy Permian-Triassic paleorift are of interest. The pre-Jurassic oil and gas complex(oil and gas bearing horizon of the contact zone— OGBHCZ and, actually, the Inner Paleozoic) is assigned along with the Cretaceous (the Neocomian), Upper Jurassic, Middle Jurassic and Lower Jurassic oil and gas complexes in the study area. It is accepted that the Upper Jurassic Bazhenov suite is the oil source formation for the Middle Jurassic, Upper Jurassic and Cretaceous oil and gas complexes, as well as Togurskaya suite — for the Lower Jurassic and pre-Jurassic deposits. Researches are carried out in the context of the methodology of the sedimentary and migrational theory of naftidogenesis. Spatiotemporal localization of the generation foci of Togurskaya oil is performed with the original method of paleotemperature modeling.